Correlation of hydrogen-bonding propensity and anticancer profile of tetrazole-tethered combretastatin analogues - Jedhe, Ganesh S.; Paul, Debasish; Gonnade, Rajesh G.; Santra, Manas K.; Hamel, Ernest; Tam Luong Nguyen; Sanjayan, Gangadhar J. (Bioorganic & Medicinal Chemistry Letters, 2013)
A series of 1,5-disubstituted tetrazole-tethered combretastatin analogues with extended hydrogen-bond donors at the ortho-positions of the aryl A and B rings were developed and evaluated for their antitubulin and antiproliferative activity. We wanted to test whether intramolecular hydrogen-bonding used as a conformational locking element in these analogues would improve their activity. The correlation of crystal structures with the antitubulin and antiproliferative profiles of the modified analogues suggested that hydrogen-bond-mediated conformational control of the A ring is deleterious to the bioactivity. In contrast, although there was no clear evidence that intramolecular hydrogen bonding to the B ring enhanced activity, we found that increased substitution on the B ring had a positive effect on antitubulin and antiproliferative activity. Among the various analogues synthesized, compounds 5d and 5e, having hydrogen-bonding donor groups at the ortho and meta-positions on the 4-methoxy phenyl B ring, are strong inhibitors of tubulin polymerization and antiproliferative agents having IC50 value in micromolar concentrations. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Colchicine; Combretastatin; Crystal; Tetrazole; Tubulin

Cyclopropane containing triterpenoids, cycloartenone, and cycloartenol: isolation, chemical transformations, and anticancer studies - Paul, Sayantan; Mandal, Kartik; Santra, Manas K.; Bhattacharya, Asish K. (ChemistrySelect, 2025)
Cycloartenone and cycloartenol, two plant-derived triterpenoids possessing cyclopropane ring were isolated from the latex of Artocarpus heterophyllus (jackfruit). Cycloartenol was chemically modified to synthesize dihydrocycloartenol via acetylation and deacetylation methodology followed by hydrogenation. Hydroxyl group present in the cycloartenol was also employed for the nitro benzoate formation. All the isolated and synthesized compounds were assayed against MCF7 breast cancer cell line for their anticancer properties.
Keywords: Anticancer studies; Artocarpus heterophyllus; Chemical transformations; Cycloartenol; Cycloartenone